AB0822 WHICH CLINICAL FACTORS INFLUENCE MINERALIZATION OF THE METACARPAL BONES AND FINGER JOINT SPACE WIDTH IN PSORIATIC ARTHRITIS?. (2nd June 2020) - Pfeil, A.; Heinz, M.; Renz, D.; Böttcher, J.; Wolf, G.; Oelzner, P.
Abstract : Background: Metacarpal bone mineral density as measured by digital x-ray radiogrammetry (DXR-BMD) and finger joint space width quantified by computer-aided joint space analysis presented computer based and observer independent parameters for the evaluation of radiographic damage of the hand skeleton. Objectives: The aim of this study was to quantify clinical parameter which potential influence periarticular mineralisation of the metacarpal bones and finger joint space width in Psoriatic Arthritis (PsA)-patients. Methods: The study includes 201 PsA-patients. All patients received a radiograph of the hand. Bone mineral density was measured by DXR (Pronosco X-Posure System™, Version 2.0; Sectra; Sweden) and finger joint space width of all finger joints were evaluated by computer-aided joint space analysis (CAJSA, Radiogrammetry Kit, Version 1.3.6; Sectra; Sweden). The Z-Score was used as an age- and gender-independent parameter for the quantification finger joint space narrowing. Results: Regarding gender, the DXR-BMD was significant reduced with -0.028 g/cm 2 in women. An equivalent significant result was evaluated for finger joint space width (Z-ScoreMCP -1.07, Z-ScorePIP -0.81 and Z-ScoreDIP -0.76). The DXR-BMD was significantly lowert (-0.011 g/cm 2 ) between the disease duration < 2 years (0.545±0.076 g/cm 2 ) and >10 years (0.509±0.070 g/cm 2 ). The Z-Score showed no significant change regarding the disease duration. Inflammatory activity as measured by c-reactive protein presented no impact on DXR-BMD and the Z-Score of all finger joints. Additionally, the use of corticosteroids was associated with a reduced DXR-BMD (-0.037 g/cm 2 ) and an absence of finger joint space narrowing. Conclusion: The study highlights that the demineralisation of the metacarpal bones was associated with female gender, disease duration and the use of corticosteroids. Whereas, the prior mentioned parameters had no influence on finger joint space width. Consequently, periarticular demineralisation and finger joint space narrowing presented two different and independent radiological signs in PsA. References: N/A Disclosure of Interests: Alexander Pfeil Grant/research support from: This study Investigator Initiated Study "Automatic assessment of joint space narrowing in rheumatoid arthritis based on the Post-hoc analysis" (number: IIS-2016-110818) is a part of the of the Investigator Initiated Study "The quantification of inflammatory related periarticular bone loss in certolizumab pegol treated patients with rheumatoid arthritis" (number: IIS-2014-101458) which is supported by UCB Pharma GmbH, Monheim, Germany., Marcus Heinz: None declared, Diane Renz: None declared, Joachim Böttcher: None declared, Gunter Wolf: None declared, Peter Oelzner: None declared